Exploring twitter discussions on healthy food: inspiring, access to healthy food for young, and nutritional economics in focus - Kvasnička, Roman; Kvasničková Stanislavská, Lucie; Pilař, Ladislav; Kuralová, Kateřina; Pilařová, Lucie; Čejka, Martin (Frontiers in Sustainable Food Systems, 2024)
Considering that food is a critical factor for a healthy population, social media analysis of discussions about this area is very important to understanding people’s behavior. This research aimed to identify the main areas of communication about healthy food, including sentiment identification, on the social network Twitter (now X). We achieved this aim by analyzing 828,963 Tweets posted from April 1, 2018 to April 17, 2023 based on a dataset that included all Tweets containing the hashtag “#healthyfood” or the phrase “healthy food”. This study extends previous research that focused only on hashtags and did not include all messages about healthy food. The results identified five main communication areas, namely 1) Inspiring, 2) Access to healthy food for children and youth, 3) Expenditure on healthy food, 4) Homemade food, and 5) Vegan/vegetarian diet, of which the second and third areas were not identified in previous research due to selective analysis focusing only on hashtags. These two communities had the highest negative sentiment of the top ten communities, suggesting that these issues require attention.